Laminar and turbulent conjugate regimes of natural convection in a square enclosure - Sheremet Мikhael Аlexandrovich (Computational Continuum Mechanics, 2012)
Mathematical simulation of laminar and turbulent regimes of unsteady conjugate natural convection in a square enclosure with heatconducting walls of finite thickness has been carried out in terms of dimensionless variables such as velocity, pressure, temperature. Results are presented in the form of contour maps for streamlines, isotherms and turbulent viscosity. The average Nusselt number at a solid-fluid interface is obtained as a function of time, Rayleigh number and thermal conductivity ratio.